2016
DOI: 10.1039/c6cp03969c
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical properties of MAPbX3 perovskites (X = I, Br, Cl): a unified DFT and GW theoretical analysis

Abstract: Materials engineering is a key for the enhancement of photovoltaics technology. This is particularly true for the novel class of perovskite solar cells. Accurate theoretical modelling can help establish general trends of behavior when addressing structural changes. Here, we consider the effects due to halide substitution in organohalide CHNHPbX perovskites exploring the halide series with X = Cl, Br, I. For this task, we use accurate DFT and GW methods including spin-orbit coupling. We find the expected band g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
135
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 39 publications
(39 reference statements)
19
135
3
1
Order By: Relevance
“…7,[24][25][26][27]29,30,58 The computational approach, whether it relies on density functional theory (DFT) with or without hybrid functionals, 29,59 GW approximation, 60 or semi-empirical modeling (e.g. k · p or tight-binding), constitutes a precious tool, combined with symmetry analysis, in the characterization of SOC-induced spin splittings.…”
mentioning
confidence: 99%
“…7,[24][25][26][27]29,30,58 The computational approach, whether it relies on density functional theory (DFT) with or without hybrid functionals, 29,59 GW approximation, 60 or semi-empirical modeling (e.g. k · p or tight-binding), constitutes a precious tool, combined with symmetry analysis, in the characterization of SOC-induced spin splittings.…”
mentioning
confidence: 99%
“…Fundamental insight of the structural dynamics holds the key to understanding their unique electronic properties, and is the subject of intensive theoretical and experimental investigations. [5][6][7][8][9][10] Methylammonium cation (CH 3 NH + 3 , MA), the most frequently incorporated A site cation in recent photovoltaic applications, possesses a large dipole and exhibits dynamic orientational disorder at room temperature. [11,12] The orientational degrees of freedom of the anisotropic organic cation have been suggested to be responsible for the excellent electronic properties of the hybrid perovskites.…”
mentioning
confidence: 99%
“…This is especially true for realistic structures in working devices, which often are compounds with mixtures of more than one organic cation, metal cation or halide anion with sophisticated surfaces and interfaces [1][2][3][4][5][6][7] . The challenges to fundamental understanding of the electronic structure of AMX 3 perovskites stem from their rich chemical and physical properties and the interplay of these properties 6,7 Several research groups [8][9][10][11][12][13][14][15][16] have successfully applied the GW method to predicting electronic structures of AMX 3 perovskites. Even et al 8 have identified the importance of a giant spin-orbit coupling (SOC) effect (about 1.0 eV) in the lead iodide perovskites, acting mainly on the conduction band (mainly consisting of Pb states).…”
mentioning
confidence: 99%